Solve for y 3*(-y)=3

Math
3⋅(-y)=3
Multiply -1 by 3.
-3⋅y=3
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3⋅y=3 by -3.
-3⋅y-3=3-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3⋅y-3=3-3
Divide y by 1.
y=3-3
y=3-3
Divide 3 by -3.
y=-1
y=-1
Solve for y 3*(-y)=3

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top